Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae) - Pinto, Ângelo Parise; Mejdalani, Gabriel; Takiya, Daniela Maeda (Zootaxa, 2017)
The taxonomy of the Proconiini genus Diestostemma Amyot & Serville is revisited and the D. bituberculatum species complex is proposed to include D. bituberculatum (Signoret), D. rubriventris (Schmidt), and four new species. A revision of this species complex includes a new geographical record for D. rubriventris and description and illustration of three Ecuadorian and one Brazilian new species based on males and females: D. albinoi sp. nov. (Ecuador: Orellana Province), D. cavichiolii sp. nov. (Brazil: Mato Grosso State), D. gervasioi sp. nov. (Ecuador: Orellana Province), and D. olivia sp. nov. (Ecuador: Orellana Province). These species, all named as homages to the treehopper specialist Dr. Albino Morimasa Sakakibara and his former students, are very similar to D. bituberculatum in general appearance, differing mainly by the shape of the male and female terminalia, but also by slight aspects of the external morphology. The status of the name-bearing specimen of D. rubriventris is modified from lectotype to holotype. The study shows that the species diversity of Diestostemma is far from being entirely known. However, several old available names should be evaluated in a full revision context before description of other new species.